Tantangan Hukum dalam Integrasi Sistem Perbankan Digital dan Keamanan Siber di Indonesia - Tambunan, Henri Marusaha; Noviarani, Devi; Damayanti, Winda Agustina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The digital transformation in the Indonesian banking sector has created significant legal challenges, especially in terms of cybersecurity and customer data protection. This study aims to analyze the complexity of legal challenges in the integration of digital banking systems and cybersecurity in Indonesia, and to identify solutions that can be applied to overcome them. The methodology used is normative legal analysis with a legislative approach and case studies. The results of the study indicate that the main challenges include regulatory compliance, customer data protection, jurisdiction in cross-border transactions, and law enforcement in cybercrime. This study found that it is necessary to strengthen regulations, increase investment in security infrastructure, and develop competent human resources to face these challenges. In conclusion, the success of the integration of digital banking systems and cybersecurity in Indonesia requires a comprehensive approach that involves collaboration between regulators, the banking industry, and other stakeholders, as well as a legal framework that is adaptive to technological developments.